Targeted mutation of the CREB gene: compensation within the CREB/ATF family of transcription factors. - Hummler, E (1994)
The cAMP response element binding protein (CREB) has been implicated as a key regulator in the transcriptional control of many genes. To assess the functional importance of CREB in vivo and its role in development, we used gene targeting to generate mice with a disruption of the CREB gene. Homozygous mutant mice appeared healthy and exhibited no impairment of growth or development. In this report we demonstrate that CREB and two other members of the CREB/ATF family, cAMP response element modulation protein (CREM) and activating transcription factor 1 (ATF1), appear to form a unique subgroup within this extensive class of transcription factors. Examination of CREM mRNA and protein levels in CREB mutant mice demonstrated overexpression of CREM in all tissues examined, but no change in ATF1 levels. These data demonstrate that CREB is not the sole mediator of cAMP-dependent transcriptional regulation and probably acts in concert with a specific subset of cAMP response element-binding proteins to transduce the cAMP signal and, in its absence, these same proteins can compensate for CREB function in vivo.